2018
DOI: 10.1007/s00441-018-2924-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing a 3D intestinal epithelium model for livestock species

Abstract: The in vitro 3D culture of intestinal epithelium is a valuable resource in the study of its function. Organoid culture exploits stem cells’ ability to regenerate and produce differentiated epithelium. Intestinal organoid models from rodent or human tissue are widely available whereas large animal models are not. Livestock enteric and zoonotic diseases elicit significant morbidity and mortality in animal and human populations. Therefore, livestock species-specific models may offer novel insights into host-patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(157 citation statements)
references
References 47 publications
1
142
0
1
Order By: Relevance
“…Moreover, the organoid epithelium polarized, acquiring morphology similar to those of the in vivo situation (Derricott et al, 2018). Bovine crypt isolation and organoid derivation required modifications from murine and bovine protocols: the bovine enteroid media was supplemented with R-spondin (Wnt agonist), Noggin (TGFβ superfamily inactivator) and EGF (to enhance epithelial proliferation) and inhibitors such as A83-01 (TGFβ type 1 receptor), SB202190 (MAP 3K), Y27632 (ROCK) and CHIR99021 (glycogen synthase kinase 3) (Derricott et al, 2018). Bovine crypt isolation and organoid derivation required modifications from murine and bovine protocols: the bovine enteroid media was supplemented with R-spondin (Wnt agonist), Noggin (TGFβ superfamily inactivator) and EGF (to enhance epithelial proliferation) and inhibitors such as A83-01 (TGFβ type 1 receptor), SB202190 (MAP 3K), Y27632 (ROCK) and CHIR99021 (glycogen synthase kinase 3) (Derricott et al, 2018).…”
Section: Bovine Intestinal Organoidsmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, the organoid epithelium polarized, acquiring morphology similar to those of the in vivo situation (Derricott et al, 2018). Bovine crypt isolation and organoid derivation required modifications from murine and bovine protocols: the bovine enteroid media was supplemented with R-spondin (Wnt agonist), Noggin (TGFβ superfamily inactivator) and EGF (to enhance epithelial proliferation) and inhibitors such as A83-01 (TGFβ type 1 receptor), SB202190 (MAP 3K), Y27632 (ROCK) and CHIR99021 (glycogen synthase kinase 3) (Derricott et al, 2018). Bovine crypt isolation and organoid derivation required modifications from murine and bovine protocols: the bovine enteroid media was supplemented with R-spondin (Wnt agonist), Noggin (TGFβ superfamily inactivator) and EGF (to enhance epithelial proliferation) and inhibitors such as A83-01 (TGFβ type 1 receptor), SB202190 (MAP 3K), Y27632 (ROCK) and CHIR99021 (glycogen synthase kinase 3) (Derricott et al, 2018).…”
Section: Bovine Intestinal Organoidsmentioning
confidence: 88%
“…Derricott and colleagues (Derricott et al, 2018) demonstrated the presence, in bovine intestinal organoids, of different types of differentiated epithelial cells showing the expression of chromogranin A, mucin 2 and E-cadherin, thus proving that the isolated crypts were capable of regeneration and differentiation (Derricott et al, 2018). This research has shown that bovine intestinal organoids can be used to obtain bovine differentiated epithelial cells (Derricott et al, 2018). This research has shown that bovine intestinal organoids can be used to obtain bovine differentiated epithelial cells (Derricott et al, 2018).…”
Section: Bovine Intestinal Organoidsmentioning
confidence: 93%
See 3 more Smart Citations